Totally ordered multicast in large-scale systems - Rodrigues, L.E.T.; Fonseca, H.; Verissimo, P. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
Totally ordered multicast protocols have proved to be extremely useful in supporting fault-tolerant distributed applications. This paper compares the performance of the two main classes of protocols providing total order in large-scale systems (token-site and symmetric protocols) and proposes a new dynamic hybrid protocol that, when applied to systems where the topology/traffic patterns are not known a priori, offers a much lower latency than any of the previous classes of protocols in isolation.